2019
DOI: 10.11646/zootaxa.4652.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Fungus-feeding thrips in Iran with a new species of Stictothrips (Thysanoptera: Phlaeothripidae)

Abstract: An illustrated key is provided to distinguish 13 genera of fungus-feeding thrips recorded from Iran in both subfamilies of Phlaeothripidae (Idolothripinae, Phlaeothripinae). Information is provided concerning 16 species recorded from this country. A curious new species of Stictothrips is described from both sexes collected from dead leaves in Fars province, southern Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 509 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, the relationships of some genera remain doubtful, including Cephalothrips, whose position is unclear. Minaei and Mound (2014) and Hakimara et al (2019) suggested that it should be considered in the Liothrips-lineage due to some structural similarities. The members of this genus may be a connecting link between the Phlaeothrips and Liothrips lineages, as they have one sense cone on antennal segment I, prosternal basantra absent, and fore wing parallel-sided (similar to Liothrips lineage), but in contrast, the forewing with duplicated cilia, and associated with dead branches, leaf litter and fungus (similar to Phlaeothrips).…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationships of some genera remain doubtful, including Cephalothrips, whose position is unclear. Minaei and Mound (2014) and Hakimara et al (2019) suggested that it should be considered in the Liothrips-lineage due to some structural similarities. The members of this genus may be a connecting link between the Phlaeothrips and Liothrips lineages, as they have one sense cone on antennal segment I, prosternal basantra absent, and fore wing parallel-sided (similar to Liothrips lineage), but in contrast, the forewing with duplicated cilia, and associated with dead branches, leaf litter and fungus (similar to Phlaeothrips).…”
Section: Discussionmentioning
confidence: 99%
“…C. sumatranus Priesner (1928) was based on a single female from Sumatra, and this is discussed further below under C. timur. The last one, C. albosignatus was recorded from Iran (Hakimara et al 2019), which seems widespread in the Mediterranean area (ThripsWiki 2023).…”
Section: Compsothrips Reutermentioning
confidence: 99%
“…Despite the considerable progress in the systematic and faunistic studies of thrips over the past 50 years, as reflected in ThripsWiki (2021) and Mound & Cavalleri (2021), the taxonomic identity and relationships of many of the major Thysanoptera groups in the family Phlaeothripidae remain enigmatic. Host-plant relationships of the many leaf-feeding species in the species-rich Liothrips-linage are largely unknown (Hakimara et al, 2019), and systematic relationships among many monotypic genera are poorly evaluated (Mound & Tree, 2021b). There are similar problems regarding fungus-feeding species in the Phlaeothrips-lineage, particularly due to the lack of field studies on many species that exhibit sexual and alary dimorphisms (Mound et al, 2020), as well as remarkable polyphenisms associated with body size (Mound & Tree, 2021a).…”
Section: Introductionmentioning
confidence: 99%